IMPROVE MATHEMATICAL LEARNING CREATIVITIES OF JUNIOR HIGH SCHOOL STUDENTS THROUGH SNOWBALL THROWING TYPE OF COOPERATIVE LEARNING MODEL - Moch Hasbi Ridlo Ma'sum; Nurkolis Nurkolis ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The overall success of the study included the level of student creativity increased, seen from the four creative indicators namely fluency (fluency), flexibility (flexibility), originality (authenticity) and elaboration (decomposition) which always experienced an increase in each cycle. In line with this research is based on problems found in schools, especially in mathematics learning needs to be pursued a learning strategy, one of which is using the cooperative type snowball throwing learning model. Based on the results of the research evaluation, it can be concluded from the results of the study that snowball throwing models can enhance students' creativity, provide a good and pleasant atmosphere, and produce a positive response to mathematics learning activities. Keywords:  Mathematical Learning Creativity and Cooperative Learning Model Type Snowball Throwing